The importance of parental human papillomavirus vaccine series initiation for reducing sex disparities in human papillomavirus vaccine series initiation among children in the United States - Elinita Pollard; Hunter K. Holt; Milkie Vu; Meng-Han Tsai (Preventive Medicine Reports)
Objective: Male children are less likely to initiate the human papillomavirus (HPV) vaccine series than their female counterparts. Furthermore, evidence suggests children with parents who initiated the vaccine series may be more likely to do the same. However, no studies have examined if parents' vaccination status modifies sex differences in HPV vaccine series initiation among children. Methods: Using the 2022 National Health Interview Survey data, we examined the association between parents' HPV vaccination status (unvaccinated, initiated the vaccine series, unknown) and sex disparities in HPV vaccine series initiation among children using weighted multivariable logistic regression models. Results: Among 2200 parent-child dyads, less than half of parents (15.6 %) and children (32.6 %) initiated the HPV vaccine series. In adjusted analysis, male children had decreased odds of vaccine series initiation (OR: 0.73, 95 % CI: 0.58, 0.92). Children with parents who initiated the vaccine series had an increased odds of initiating the vaccine series compared to those whose parents were unvaccinated (OR: 2.88, 95 % CI: 2.00, 4.15). When stratified by parent's HPV vaccine series initiation, male children only had a decreased odds of HPV vaccine series initiation among children with unvaccinated parents (OR: 0.69, 95 % CI: 0.54, 0.89). Conclusion: Male children were only less likely to initiate the HPV vaccine series among children whose parents were unvaccinated against HPV. Thus, healthcare providers should engage both the parent and child in the vaccine recommendation process. Doing so may improve HPV vaccine series initiation for parents who are within the recommended age range and male children.